PENINGKATAN MINAT LITERASI AKUNTANSI DAN KEUANGAN PADA SISWA LPK SAKURA EDUCATION - Laily Ramadhani; Siswanto; Marliyoni Halawa (Publikasi Kegiatan Pengabdian Masyarakat Widya (PUNDIMASWID), 2025)
This Community Service activity aims to introduce financial literacy programs for students. Literacy education is important for students so that they are accustomed to managing finances well in the future. In Indonesia, financial literacy education is still very rare, both in the family and school environment, the provision of education about financial literacy has not been carried out seriously and planned. This service is expected to be useful for simple financial management knowledge for early childhood through the "savings" pattern. The dedication material is focused on how to introduce the concept of money, its use and when to shop. Financial literacy education will be carried out for students at LPK Sakura Education. The teaching method is carried out with a mentoring method by the Teaching Team. The teaching method uses simulations and learning using educational films on financial literacy as well as movements and songs Let's Save. The savings simulation is carried out by practicing saving using piggy banks distributed to students. Mentoring from the teaching team is carried out continuously with the introduction of financial literacy education that can benefit early childhood and benefit themselves, families and society in the future. The results of this community service demonstrated active student participation, with 10 students asking questions about financial literacy, and 3 teachers asking questions about the role of teachers and schools in helping students learn to save. These questions sparked active interaction between the resource person and participants, interspersed with games to liven up the atmosphere. Keywords: Accounting Literacy, Finance, Students